PENCEGAHAN PENYEBARAN PAHAM RADIKALISME OLEH DENSUS 88 ANTI TEROR POLRI GUNA MENANGKAL AKSI TERORISME DEMI TERWUJUDNYA KAMTIBMAS DI WILAYAH HUKUM PROVINSI BALI - Kusuma , Made Rama Suria Adi (Kerta Dyatmika, 2025)
History serves as a reminder that dark chapters must never be repeated. In the context of Bali Province, the threat of radicalism and terrorism remains a pressing concern that necessitates preventive measures to ensure public safety and social order. This study aims to analyze the preventive efforts undertaken by the Indonesian National Police's Counter-Terrorism Special Detachment 88 (Densus 88 Anti-Terror) in countering the spread of radical ideologies in Bali, as well as to identify the challenges encountered in the implementation of such efforts. The research employs an empirical method with a descriptive approach, utilizing primary, secondary, and tertiary data sources. Data were collected through observation, interviews, and documentation, and subsequently analyzed qualitatively and presented in a descriptive-analytical format. The findings indicate that preventive measures include enhanced intelligence and surveillance, collaboration with local stakeholders, implementation of deradicalization programs, education and outreach initiatives, pre-emptive operations to disrupt potential terrorist activities, and regulatory reinforcement. However, Densus 88 faces several challenges, such as the high mobility and diversity of residents and tourists, the use of digital technology and social media by radical groups, inter-agency coordination barriers, human rights concerns, limited public awareness regarding the dangers of radicalism, as well as ideological and economic factors that facilitate the proliferation of radical ideologies, including the emergence of "lone wolf" threats. In conclusion, while significant strategic efforts have been made, the effectiveness of radicalism prevention requires sustained inter-sectoral synergy, greater public understanding, and the strengthening of early detection systems.